Student Perceptions of Public Health Students' Staying Up late at Night - Fanny Arya Rahmasari; Putra Siregar, Apriadi (Pena Cendekia Insani, 2024)
This research was conducted to look at the perceptions of public health students towards the behavior of students staying up late. The research was carried out using a qualitative method, for 5 FKM student respondents class of 2020 the data collection process was carried out using a questionnaire through in-depth interviews. The results showed that students in this study had good knowledge of the meaning of staying up late, students understood what was meant by staying up late and had knowledge and perceptions of the dangers of staying up late. activities and demands that must be carried out so that the body cannot rest properly and is deprived of sleep, students have the perception that staying up late does have a harmful impact on health and they feel the negative impact such as fatigue, lack of concentration and understand the impact of staying up late on increasing the risk of diseases such as diabetes, heart disease and decreased immune system, but in this study all students did the activity of staying up late intensity often and very often and sleeping 5-6 / less than 5 hours and even just starting to sleep at 1-3 in the morning, many factors influence the behavior of staying up late such as piling up of tasks and short deadlines, organizational activities, stress, unimportant activities such as drakor, gadgets and social media. Even though students understand the meaning of staying up late, students have the perception that it is difficult for students to avoid the habit of staying up late.